Assessing the phytotoxicity of cetrimonium bromide in plants using eco-physiological parameters. Issue 1 (December 2016) - Song, Uhram; Kim, Han
Abstract Background Although cetrimonium bromide is widely used for its bactericidal effects, the safety of cetrimonium bromide remains controversial. Therefore, the phytotoxicity of cetrimonium bromide was tested to evaluate its acute toxicity to plants and possible toxicity to other organisms and the ecosystem. Results The germination rates of two test species, Lactuca sativa and Brassica campestris, were significantly decreased after cetrimonium bromide treatment. Furthermore, cetrimonium bromide treatment at over 1 mg/L concentration significantly affected root elongation immediately after germination. In pot experiments with semi-mature plants, significantly decreased shoot elongation and chlorophyll content were detected in both species following cetrimonium bromide treatment. Cetrimonium bromide treatment also significantly increased the antioxidant enzyme activities of plants. Conclusion Our results show that cetrimonium bromide is phytotoxic, and since phytotoxicity testing can imply potential toxicity in the environment, further studies of the environmental toxicity of cetrimonium bromide should be performed.